Structure and preparation method of a new type of absorbing material

By combining conductive polymer nanotubes with metal magnetic nanoparticles to form nanocomposites, the problems of low magnetic permeability and reduced conductivity of traditional materials are solved, and efficient electromagnetic wave absorption and widening the absorption frequency band are achieved.

CN115119491BActive Publication Date: 2025-02-18UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210742378.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-28
Publication Date
2025-02-18
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

The magnetic permeability of traditional conductive polymer materials is low, resulting in a narrow absorption frequency band, and nanostructured absorbing materials may greatly reduce their conductivity after being recombined with inorganic nanoparticles.

Method used

By compounding the conductive polymer nanotubes with metal magnetic nanoparticles, the metal magnetic nanoparticles are bonded to the surface of the conductive polymer nanotube by chemical self-assembly method to form a nanocomposite.

Benefits of technology

It realizes the high dielectric constant and high magnetic permeability of the material, meets the impedance matching conditions, widens the absorbing frequency band, enhances the absorbing efficiency, and has the "light, thin, wide and strong" absorption characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115119491B_ABST
    Figure CN115119491B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of novel wave absorbing materials, and relates to a structure and preparation method of a novel wave absorbing material; the wave absorbing material is based on conductive polymer nanotubes, and metal magnetic nanoparticles are composited on the outer surface, and the metal magnetic nanoparticles are bonded to the surface of the conductive polymer nanotubes by chemical self-assembly. The advantages of the present invention are: the morphology of conductive polymer nanotubes (PPy, PANI, PEDOT, PT, etc.) is regulated to obtain conductive polymer nanotubes with good morphology, and then the nanotubes are chemically bonded with metal magnetic nanoparticles by chemical self-assembly to obtain nanocomposites, which have both high dielectric constant and high magnetic permeability, not only meet the electromagnetic matching principle, but also enable more electromagnetic waves to enter the interior of the material, and also enable the wave absorbing mechanism to change from a single electric loss type or magnetic loss type to two types, and increase the interface, and then combine the nano effect to enable the composite material to achieve the purpose of broadening the wave absorbing frequency band and enhancing the wave absorbing efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of novel absorbing materials, and relates to a structure and a preparation method of a novel absorbing material; specifically, it relates to a composite structure of a conductive polymer nanotube / metal magnetic nanoparticle composite and a method for preparing the composite by chemical self-assembly to prepare the conductive polymer nanotube and the metal magnetic nanoparticle by nanocompositing. Background Art

[0002] In recent years, with the rapid development of modern electronic industry and communication industry, various digital and high-frequency electronic and electrical equipment used in the electromagnetic wave range of 1-40GHz has increased day by day, resulting in electromagnetic wave radiation becoming a new social hazard. The electromagnetic interference caused by electromagnetic wave radiation affects the normal operation of nearby equipment. It is estimated that the economic losses caused by failures of electronic and electrical equipment worldwide due to electromagnetic wave interference are as high as 500 million US dollars each year. Scientific research has also confirmed that long-term exposure to electromagnetic wave radiation environment will damage physical and mental health. The use of absorbing materials is an effective means to reduce or eliminate electromagnetic wave interference.

[0003] Absorbing materials also play a huge role in military stealth technology. For example, the U-2 high-altitude reconnaissance aircraft and F-117 stealth fighter of the United States are good applications of absorbing materials. One of the cores of modern defense electronic countermeasure technology is to release strong electromagnetic waves with wide frequencies to destroy the opponent's military facilities. The acquisition and counter-acquisition of information has become the focus of war. Therefore, the development of new absorbing materials has also become a very urgent issue in modern protection engineering. At present, the development of lightweight, high shielding efficiency and good mechanical properties of electromagnetic shielding materials, and the realization of "light, thin, wide, strong" structural function integration and intelligent new absorbing materials are important development directions in the field of electromagnetic shielding. In recent years, conductive polymers such as polypyrrole, polyaniline, polythiophene, etc. have attracted widespread attention as absorbing materials due to their unique advantages such as low density, diversified structure, adjustable electromagnetic parameters, and easy composite processing.

[0004] Electromagnetic wave loss in materials occurs mainly in three ways: first, reflection attenuation on the incident surface; second, absorption attenuation of the electromagnetic wave material entering the shield; and third, multiple reflection attenuation inside the shield [Electromagnetic Wave Shielding and Absorbing Materials (Second Edition), Chemical Industry Press, 2013].

[0005] In order for absorbing materials to effectively absorb electromagnetic waves and convert them into heat for dissipation, the incident waves should first be allowed to enter the material as much as possible. According to electromagnetic theory, absorbing materials should meet the impedance matching condition, that is, the magnetic permeability (μ r) and dielectric constant (ε) as close as possible. Studies have shown that conductive polymer materials are electrical loss absorbers, and their maximum attenuation and dielectric constant increase with increasing conductivity. However, the magnetic permeability of traditional conductive polymer materials is very low, resulting in a relatively narrow absorption band.

[0006] Nanostructuring of absorbents is an important way to further improve the absorption performance. Due to the large specific surface area of ​​nanomaterials, interface polarization and multiple scattering become important absorption mechanisms, allowing more electromagnetic waves to enter the material and be absorbed. The quantum effect of nanomaterials also causes the energy levels of nanoparticles to split, and the interval between the split energy levels is in the energy range corresponding to microwaves (10 -2 ~10 -5 eV), which leads to a new absorption mechanism and further improves the absorption performance.

[0007] The shapes and sizes of conductive polymer materials in composite materials in current literature are basically microspheres or particles with diameters of hundreds of nanometers to several micrometers, or even tens of micrometers. This not only causes poor solubility of the material and poor processability, but also may greatly reduce conductivity after being composited with inorganic nanoparticles.

[0008] The conductive polymer / magnetic nanoparticle composite absorbents reported so far are basically made of Fe 3 O 4 Or oxide magnetic nanoparticles such as barium ferrite and manganese ferrite, the selection of magnetic components is very simple. In fact, according to the results of magnetic research, the magnetic permeability of oxide magnetic materials is low and the magnetic anisotropy is small, which is far inferior to metal alloy magnetic materials. For example, the Ms of CoFe alloy is as high as 240emu / g, which is much higher than Fe 3 O 4 The saturation magnetization is 93emu / g. The high saturation magnetization of magnetic metal materials gives them a higher magnetic permeability, which may produce a relatively strong wave absorption intensity. The bulk magnetic metal material will greatly reduce its wave absorption performance due to the eddy current effect. The way to solve this problem is to make the magnetic metal material into nanometer size. If there is only one component of the absorbing material, the metal magnetic nanomaterial, because the component is too single and the wave absorption mechanism only comes from magnetic loss and nanometer effect, it will cause the disadvantage of too narrow absorption band. Therefore, the present application combines it with an electrically lossy component (carbon material, conductive polymer material, etc.) to have both high dielectric constant and high magnetic permeability, thereby overcoming the shortcomings of existing materials and giving full play to the wave absorption performance of the material. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a structure of a new type of absorbing material and a preparation method. The method is used to prepare a conductive polymer nanotube / metal magnetic nanoparticle composite material. The conductive polymer nanotube and the metal magnetic nanoparticle in the composite nanomaterial are bound by coordination bonds and are environmentally stable. The composite nanomaterial is a new type of broadband and efficient nanocomposite absorbing material. The nanocomposite structure can obtain a very high dielectric constant and magnetic permeability, and has a unique nano effect, and is suitable for use in military stealth materials and electromagnetic shielding applications.

[0010] The present invention is achieved through the following technical solutions:

[0011] A novel wave absorbing material, the microstructure of which is based on conductive polymer nanotubes, the outer surface of which is chemically compounded with metal magnetic nanoparticles; the metal magnetic nanoparticles are bonded to the surface of the conductive polymer nanotubes through a ligand substitution reaction. In view of the technical problem that the magnetic permeability of traditional conductive polymer materials is very low, resulting in a relatively narrow absorption band, the present invention compounds conductive polymer nanotubes with metal magnetic nanoparticles, which can not only increase the magnetic permeability (μ r ) and dielectric constant (ε) are close, which meets the impedance matching condition, thereby improving the microwave absorptivity of the material. It can also transform the traditional single electric loss type or magnetic loss type into two microwave loss types, electric loss type and magnetic loss type. In addition, by regulating the morphology of the conductive polymer, it is prepared into a one-dimensional hollow structure of nanotubes, which increases the multiple scattering effect and further increases the loss of electromagnetic waves, making it produce lightweight and broadband microwave absorption characteristics.

[0012] Furthermore, the conductive polymer nanotube is made of conductive polymer material, including any one of polypyrrole PPy, polyaniline PANI, polyethylene dioxythiophene PEDOT, and polythiophene PT; the conductive polymer nanotube has a one-dimensional cavity structure, and the cavity diameter is 100-400nm; during the preparation process of the conductive polymer nanotube, the diameter can be adjusted between 100 and 400nm, so that the tube diameter of the absorbing material can be adjusted according to the needs of actual application.

[0013] The conductive polymer nanotube has a one-dimensional cavity structure, and the cavity structure is conducive to improving the wave absorption efficiency, because the microstructure of multiple pores and cavities can form multiple scattering points, and the electromagnetic waves will consume energy through multiple scattering, thereby achieving the purpose of enhancing the absorption capacity and broadening the wave absorption band. Compared with the traditional technology, the core-shell structure in which the magnetic nanoparticles are embedded in the conductive polymer material hinders the reversal of the magnetic moment, resulting in the reduction of the coercive force and saturation magnetization intensity of the magnetic nanoparticles, and the magnetic loss is significantly reduced, so that the wave absorption capacity of the composite material cannot be maximized. In the present invention, on the basis of retaining the cavity structure of the conductive polymer core-shell material, the magnetic particle core is taken out and bonded to the microstructure of the surface of the conductive polymer nanotube with the cavity structure, which will be conducive to maintaining the high magnetic permeability of the material.

[0014] Furthermore, the metal magnetic nanoparticles are any one of CoFe, FePt, Co, NiFe, NiPt, Ni, FePd and FeRu particles, wherein the component ratio of CoF, FePt, NiFe, NiPt, Ni, FePd and FeRu particles can be regulated; and the particle size of the metal magnetic nanoparticles is below 10nm. The nano-size of the metal magnetic particles can overcome the eddy current effect of bulk metal materials under high-frequency electromagnetic waves, providing the possibility of further increasing the microwave absorption efficiency of the composite material.

[0015] A method for preparing a novel absorbing material, used for preparing the novel absorbing material, the method comprising the following steps:

[0016] (1) preparing conductive polymer nanotubes by a microemulsion method, wherein the prepared conductive polymer nanotubes include polypyrrole PPy conductive polymer nanotubes, polyaniline PANI conductive polymer nanotubes, polyethylene dioxythiophene PEDOT conductive polymer nanotubes or polythiophene PT conductive polymer nanotubes;

[0017] (2) preparing metal magnetic nanoparticles by a high temperature liquid phase method, wherein the prepared metal magnetic nanoparticles include CoFe metal magnetic nanoparticles, NiFe metal magnetic nanoparticles, FePt metal magnetic nanoparticles, Co metal magnetic nanoparticles, NiPt metal magnetic nanoparticles, Ni metal magnetic nanoparticles, FePd metal magnetic nanoparticles or FeRu metal magnetic nanoparticles;

[0018] (3) The conductive polymer nanotubes and metal magnetic nanoparticles prepared in step (1) and step (2) are mixed in n-hexane solvent by magnetic stirring at room temperature. Since the conductive polymer reacts on the surface of the metal magnetic nanoparticles, the metal magnetic nanoparticles are bonded to the surface of the conductive polymer nanotubes, thereby obtaining a composite absorbing material with the conductive polymer nanotubes as the matrix and the metal magnetic nanoparticles as the outer surface.

[0019] Furthermore, in step (1), when the material of the prepared conductive polymer nanotubes is polypyrrole PPy, the specific preparation method is: 9 g of sodium di-(2-ethylhexyl) sulfosuccinate (AOT) and 40 mL of n-hexane are placed in a beaker, and magnetic stirring is used to mix evenly to obtain a n-hexane solution of sodium di-(2-ethylhexyl) sulfosuccinate; 9 mmol of FeCl 3 The mixture was dissolved in 0.5-1.0 mL of deionized water to prepare an aqueous solution, and then slowly added dropwise to the n-hexane solution of AOT, stirred for more than 2 hours, and then 0.5 g of pyrrole monomer Py was added dropwise, and the reaction was carried out by magnetic stirring. The reaction temperature was always controlled at 10-15 ° C. The product was centrifuged and washed, and then washed with ethanol and deionized water in turn until the filtrate was colorless, and dried in a vacuum dryer to obtain a black powder, which is polypyrrole Ppy nanotubes.

[0020] In the above process, the temperature is controlled at 10-15°C, and the surfactant AOT is added as a dopant in an "oil-in-water" environment, and Py is oriented and arranged at the interface of oil and water to form a one-dimensional nanostructure reactor. 3 Using Fe as an oxidant 3+ The oxidizing property of pyrrole causes the oxidation at the interface to initiate polymerization to generate PPy, resulting in PPy nanotubes with uniform diameter. The outer diameter of the PPy conductive polymer nanotubes can be adjusted in the range of 100nm to 400nm by adjusting the oil / water volume ratio.

[0021] Furthermore, the diameter of PPy conductive polymer nanotubes can be adjusted by changing the dissolved oxidant FeCl 3 The volume of deionized water is adjusted to adjust the oil phase / water phase volume ratio so that the outer diameter of the PPy conductive polymer nanotubes can be adjusted in the range of 100nm-400nm.

[0022] Several other conductive polymer nanotubes, such as PANI nanotubes, PEDO or PT nanotubes, can be prepared by similar methods in references ([1] Hangjun Ding, Jiaoyan Shen, Meixiang Wan, Zhaojia Chen, Formation Mechanism of Polyaniline Nanotubes by a Simplified Template-Free Method, Macromolecular Chemistry and Physics, 2008, 209, 864–871); [2] Xinyu Zhang, Jeong-Soo Lee, Gil S. Lee, Dong-Kyu Cha, Moon J. Kim, Duck J. Yang, and Sanjeev K. Manohar, Chemical Synthesis of PEDOT Nanotubes, Macromolecules, 2006, 39, 470-472.)

[0023] Furthermore, in step (2), when the prepared metal magnetic nanoparticles are CoFe metal magnetic nanoparticles, the specific method of preparing the metal magnetic nanoparticles by combining high temperature liquid phase reduction and high temperature liquid phase decomposition is as follows: 30 mL of diphenyl ether, 1 mmol of FeCl 2 ·4H 2 O and 3mmol triphenylphosphine, heated to 100℃ under Ar gas protection, then added 1mmol oleic acid, continued to heat to 200℃, and then took 2.5mL of 1mol.L -1 LiHBEt 3 The THF solution was quickly injected into the reaction vessel. When the white smoke dissipated, the temperature was raised to 240°C. When the temperature reached 240°C, 1 mmol Co was dissolved in the THF solution dropwise with a syringe. 2 (CO) 8 The diphenyl ether solution is added dropwise to the reaction container and stirred rapidly. After the reaction refluxes, the heating is stopped and the mixture is cooled to room temperature. Ethanol is added to agglomerate the nanoparticles, and the mixture is centrifuged and the supernatant is discarded. Then, n-hexane is added to the precipitate to redissolve the precipitate, and the supernatant is taken after centrifugation to obtain CoFe alloy magnetic nanoparticles.

[0024] Among them, Co 2 (CO) 8 The preparation method of diphenyl ether solution is as follows: take an appropriate amount of Co 2 (CO) 8 , add 60℃ diphenyl ether to dissolve it, and wait for Co 2 (CO) 8After complete dissolution, Co 2 (CO) 8 solution; the concentration of which can be added according to the desired composition ratio of the CoFe alloy nanoparticles;

[0025] This method is also applicable to the preparation of NiFe alloy nanoparticles, except that when preparing NiFe nanoparticles, Ni(CO) 4 As the Ni precursor, the rest of the process is exactly the same as the above-mentioned process for preparing CoFe nanoparticles.

[0026] Among other metal magnetic nanoparticles, Co and Ni single-component metal magnetic nanoparticles are easy to prepare. According to the literature, they can be prepared by either high-temperature liquid phase reduction or high-temperature liquid phase decomposition. FePt, NiPt, FePd and FeRu alloy nanoparticles can be prepared by a combination of high-temperature liquid decomposition and high-temperature liquid reduction, or by a high-temperature liquid phase co-reduction method [1. Sun SH, Anders S, Thomson T, Baglin JEE, Toney MF. Controlled synthesis and assembly of FePt nanoparticles. J. Phys. Chem. B 2003, 107: 5419-5425. 2. Sun SH, Murray CB, Weller D, et al. Monodisperse FePt nanoparticles and ferromagnetic FePt nanocrystal superlattices. Science 2000, 287: 1989-1992]. Since the magnetic properties of prepared metal magnetic nanoparticles such as Co, CoFe, NiFe, FePt, NiPt, FePd and FeRu are weak, they need to be heat treated to transform their magnetic properties from superparamagnetism to ferromagnetism. After heat treatment, the magnetic properties of the composite PPy / metal magnetic nanoparticles are more significantly improved, which helps to improve the microwave absorption performance.

[0027] Furthermore, the composite absorbing material prepared in step (3) is subjected to vacuum heat treatment or inert gas protection heat treatment below 200° C. to further improve magnetic properties and enhance absorbing performance. The maximum reflection loss of the obtained composite absorbing material is above -40 dB, and the bandwidth less than -10 dB is above 4 dB.

[0028] The invention discloses an application of a novel absorbing material, wherein the absorbing material can be applied to electromagnetic shielding materials, military stealth materials, electrode materials, molecular wires, sensors, and supercapacitors.

[0029] Beneficial technical effects of the present invention:

[0030] The method of the present invention regulates the morphology of conductive polymer nanotubes (PPy, PANI, PEDOT, PT, etc.) to obtain conductive polymer nanotubes with good morphology, and then chemically bonds the conductive polymer nanotubes with metal magnetic nanoparticles by a chemical self-assembly method to obtain a nanocomposite. The obtained composite has both high dielectric constant and high magnetic permeability, not only meets the electromagnetic matching principle and enables more electromagnetic waves to enter the interior of the material, but also enables the wave absorption mechanism to be changed from the traditional single electric loss type or magnetic loss type to both electric loss type and magnetic loss type, and increases the interface. After combining the nano effect, the material achieves the purpose of broadening the wave absorption band and enhancing the wave absorption efficiency; by regulating the morphology of the conductive polymer of the electrical component, changing it from a granular state to a one-dimensional hollow structure, and changing the type of the magnetic component and the way the two are combined, the wave absorption potential of this type of material is fully exerted, high wave absorption performance is achieved, and the "light, thin, wide and strong" wave absorption characteristics are realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a transmission electron microscope image of the sample of the PPy / CoFe magnetic nanocomposite material prepared in Example 1;

[0032] Figure 2 is the reflection loss (RL) of the PPy / CoFe magnetic nanocomposite material (20wt%, outer diameter <200nm) obtained in Example 1;

[0033] Figure 3 This is the reflection loss (RL) of the PPy / CoFe magnetic nanocomposite material (20wt%, outer diameter <200nm) after heat treatment at 150°C for 30min. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] On the contrary, the present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention as defined by the claims. Further, in order to make the public have a better understanding of the present invention, some specific details are described in detail in the detailed description of the present invention below. Those skilled in the art can fully understand the present invention without the description of these details.

[0036] Example 1

[0037] This embodiment provides a method for preparing a novel absorbing material, the method comprising the following steps:

[0038] (1) Preparation of conductive polymer nanotubes: The conductive polymer nanotubes are prepared by using the method in the literature [Jyongsik Jang and Hyeonseok Yoon, Facile fabrication of polypyrrole nanotubes using reverse microemulsion polymerization, Chem. Commun., 2003, 720-721]. The material of the conductive polymer nanotubes is polypyrrole PPy conductive polymer nanotubes. A specific preparation method is as follows:

[0039] 9.0 g AOT and 40 mL n-hexane were placed in a beaker and stirred magnetically for 10 minutes to obtain an AOT n-hexane solution. 3 Dissolve in 1.0 mL of deionized water to prepare FeCl 3 The aqueous solution was slowly added dropwise (about 5 seconds / drop) to the n-hexane solution of AOT, and after stirring for 2 hours, 0.5 g of Py was added dropwise, and the reaction temperature was controlled at 10-15°C. After magnetic stirring for 24 hours, the product was centrifuged and washed with deionized water and ethanol respectively until the filtrate was colorless, and dried in a vacuum dryer to obtain a black product, which was PPy.

[0040] The temperature was controlled at 5-10°C, and the surfactant AOT was added as a dopant in an "oil-in-water" environment. Py was oriented and arranged at the interface between oil and water to form a one-dimensional nanostructure reactor. 3 Using Fe as an oxidant 3+ The oxidizing property of pyrrole causes the oxidation at the interface to initiate polymerization to generate PPy, resulting in PPy nanotubes with uniform diameter. The outer diameter of PPy can be adjusted in the range of 100nm to 400nm by adjusting the oil / water volume ratio.

[0041] (2) The specific preparation method of CoFe metal magnetic nanoparticles is:

[0042] In a four-necked round-bottom flask, add 20 mL of diphenyl ether and 1.00 mmol of FeCl 2 ·4H 2 O, 3.00mmol triphenylphosphine, heated to 100℃ under Ar gas protection, then 1.00mmol oleic acid was added to the flask, and continued to heat to 200℃, then 2.5mL of reducing agent LiHBEt 3 (1M THF) was quickly injected into the flask. When the white smoke dissipated, the temperature rose to 240°C. In another small weighing bottle, 1.00 mmol of Co 2 (CO) 8 , add 10mL of diphenyl ether to dissolve it, and wait for Co2 (CO) 8 After complete dissolution, inject the solution dropwise into a four-necked round-bottom flask with a syringe and stir rapidly. The solution will turn black and generate a large amount of white smoke. After the solution is allowed to react and reflux for 30 minutes, stop heating and cool to room temperature. Add ethanol to aggregate the nanoparticles, centrifuge, discard the supernatant, then add n-hexane, centrifuge and take the supernatant, which is the nanoparticle solution.

[0043] Since the nanoparticles prepared in the organic phase are small and uniform, they are easier to be compounded with polymer materials at the nanoscale. The component ratio of CoFe metal alloy magnetic nanoparticles can be controlled, see the table below:

[0044] Relationship between the composition of CoFe nanoparticles and the ratio of precursors

[0045] Precursor feed molar ratio (in terms of Co:Fe atoms) sample 1:1 <![CDATA[Co 46 Fe 54 ]]> 0.43:1 <![CDATA[Co 35 Fe 65 <!-- 5 -->]]> 2.3:1 <![CDATA[Co 67 Fe 33 ]]>

[0046] (3) The prepared polypyrrole nanotubes and CoFe magnetic particles are dispersed in n-hexane in a certain ratio and magnetically stirred at room temperature for 4 hours to allow the magnetic nanoparticles to bond to the surface of the nanotubes and to form coordination bonds with the heteroatoms on the surface of the nanotubes to form a nanocomposite.

[0047] After the reaction is completed, the solution is stopped and then centrifuged, and impurities are washed with n-hexane and anhydrous ethanol respectively, and finally a black powdery substance, namely the PPy nanotube / CoFe magnetic nanoparticle composite material, is obtained.

[0048] In step (1), FeCl 3 As an oxidant, Fe 3+ The oxidizing property of Py can induce the polymerization reaction of Py to generate PPy, and PPy nanotubes with uniform diameter can be obtained. 3 The amount of can adjust the outer diameter of the conductive polymer nanotube to the range of 100nm to 400nm, specifically:

[0049] The diameter of polypyrrole nanotubes was regulated by controlling the concentration of oxidant. (Experimental conditions: 0-5℃, reaction time: 24h) 3 The amount of water in the reaction system can be changed to adjust the volume ratio of water / oil, thereby regulating the diameter of the polypyrrole nanotubes.

[0050] Group Water volume / mL <![CDATA[V 水 / V 正己烷 ]]> Nanotube outer diameter 1 0.5 5 / 400 400~500nm 2 0.7 7 / 400 200~250nm 3 1.0 10 / 400 140~150nm 4 1.2 12 / 400 <100nm

[0051] In the polypyrrole nanotube / CoFe magnetic particle composite material prepared in this embodiment, the outer diameter of the polypyrrole nanotube is less than 100nm, and the tube surface is smooth; the diameter of the CoFe magnetic particles is 5-6nm, the particle size distribution is concentrated, and they are evenly bonded to the surface of the polypyrrole nanotube. Figure 1The experimental method is simple and the experimental conditions are easy to achieve.

[0052] like Figure 2 As shown: the reflection loss (RL) of PPy / CoFe (20wt%) obtained in this example. 20 (mass fraction) of the PPy / CoFe nanocomposite was taken and mixed with 80 (mass fraction) of paraffin wax, and then pressed into a coaxial sample in a special mold, with an outer diameter of 7.00mm, an inner diameter of 3.00mm, and a thickness of 3mm. The sample absorption performance was tested using an Agilent N5244A vector network analyzer in the high frequency range of 2 to 18GHz. Figure 2 As shown in the figure, when the sample thickness is 2mm, the reflection loss (RL) is the largest at 15.45GHz. max It is -30.10dB, the frequency band with reflection loss greater than 10dB is 12~18GHz, and the bandwidth is 6GHz; the frequency band with reflection loss greater than 5dB is 10-18GHz, and the bandwidth is 8GHz.

[0053] Example 2

[0054] This embodiment provides a method for synthesizing polyaniline nanotubes / Fe by chemical self-assembly 3 The method of Pt magnetic particle composite material. Metal alloy nanoparticles with a diameter of about 4nm were prepared by improving the literature method. 30mL of diphenyl ether and 0.6mmol of FeCl were added to a four-necked round-bottom flask. 2 ·4H 2 O, heated to 150°C under Ar gas to dissolve as much as possible, then lowered the reaction temperature to 80°C, added 0.2 mmol of Pt(acac) 2 , 1.6mmol of dodecanediol and surfactants 0.5mmol of oleic acid and 0.5mmol of oleylamine, continue heating to 220℃. Use a syringe to take 3.0mL of lithium triethylborohydride (1M tetrahydrofuran) solution and add it dropwise to the flask. Then reflux at 250℃ for 30 minutes, finally stop heating and cool to room temperature. After adding ethanol, centrifuge, discard the supernatant, add n-hexane to dissolve the black precipitate, and obtain Fe 3 Pt nanoparticles.

[0055] Then, Fe 3 The n-hexane solution of Pt magnetic nanoparticles and polyaniline nanotubes were dispersed and mixed in a certain proportion, magnetically stirred for 2 hours, and finally centrifuged and dried to obtain aniline nanotubes / Fe 3 Pt nanoparticle composites.

[0056] This experimental scheme can be used in the following examples: the conductive polymer nanotubes and metal magnetic nanoparticles involved can be prepared using the conventional techniques in the present invention.

[0057]

[0058] Example 3

[0059] In order to further improve the absorbing performance of the material, the PPy / CoFe composite absorbing material in Example 1 was annealed in a vacuum at 150°C for 30 minutes with a vacuum degree of 5*10 -5 Pa. The reflection loss (RL) of PPy / CoFe (20 wt%) after annealing was tested by the method in Example 1. Figure 3 As shown in the figure, the wave absorption intensity and effective wave absorption intensity of the samples are significantly improved, and the wave absorption intensity of the samples with a thickness of 2-3mm is significantly greater than -30dB. The experimental results show that appropriate vacuum heat treatment can significantly improve the internal structure of the material, thereby enhancing the wave absorption performance.

[0060] The advantages of the present invention are: the morphology of conductive polymer nanotubes (PPy, PANI, PEDOT, PT, etc.) is regulated to obtain conductive polymer nanotubes with good morphology, and then the conductive polymer nanotubes are chemically bonded with metal magnetic nanoparticles by a chemical self-assembly method to obtain a nanocomposite with high dielectric constant and high magnetic permeability, which not only meets the electromagnetic matching principle and enables more electromagnetic waves to enter the interior of the material, but also enables the wave absorption mechanism to be changed from a single electric loss type or magnetic loss type to two types, and increases the interface. Combined with the nano effect, the composite material can achieve the purpose of broadening the wave absorption band and enhancing the wave absorption efficiency.

Claims

1. A method for preparing a novel absorbing material, characterized in that: The method comprises the following steps: (1) preparing conductive polymer nanotubes by a microemulsion method, wherein the prepared conductive polymer nanotubes include polypyrrole PPy conductive polymer nanotubes, polyaniline PANI conductive polymer nanotubes, polyethylene dioxythiophene PEDOT conductive polymer nanotubes or polythiophene PT conductive polymer nanotubes; (2) preparing metal magnetic nanoparticles by a high temperature liquid phase method, wherein the prepared metal magnetic nanoparticles include CoFe metal magnetic nanoparticles, NiFe metal magnetic nanoparticles, FePt metal magnetic nanoparticles, NiPt metal magnetic nanoparticles, FePd metal magnetic nanoparticles or FeRu metal magnetic nanoparticles; (3) mixing the conductive polymer nanotubes and metal magnetic nanoparticles prepared in step (1) and step (2) at room temperature by magnetic stirring, so that the two undergo a ligand substitution reaction, and the metal magnetic nanoparticles are bonded to the surface of the conductive polymer nanotubes, thereby obtaining a composite wave absorbing material having the conductive polymer nanotubes as a matrix and the metal magnetic nanoparticles bonded to the outer surface; The composite absorbing material prepared in step (3) is further improved in magnetic properties and enhanced in absorbing performance by vacuum heat treatment or inert gas protection heat treatment below 200°C. The maximum reflection loss of the composite absorbing material obtained is above -40dB, and the bandwidth less than -10db is above 4dB.

2. The method for preparing a novel absorbing material according to claim 1, characterized in that: In step (2), when the prepared metal magnetic nanoparticles are CoFe metal magnetic nanoparticles, the specific preparation method is to use a method combining high-temperature liquid phase reduction and high-temperature liquid phase decomposition: 30 mL of diphenyl ether, 1 mmol of FeCl2·4H2O and 3 mmol of triphenylphosphine are added in sequence, heated to 100°C under Ar gas protection, then 1 mmol of oleic acid is added, and the heating is continued to 200°C, and then 2.5 mL of a THF solution of LiHBEt3 with a concentration of 1 mol.L-1 is quickly injected into the reaction container, and when the white smoke is gone, the temperature is raised to 240°C. When the temperature reaches 240°C, a diphenyl ether solution containing 1 mmol of Co2(CO)8 is added dropwise to the reaction container with a syringe and stirred rapidly. After the reaction refluxes, the heating is stopped and the nanoparticles are cooled to room temperature; ethanol is added to agglomerate the nanoparticles, centrifuged and separated, and the supernatant is discarded; then n-hexane is added to the precipitate to redissolve the precipitate, and the supernatant is taken after centrifugation to obtain CoFe alloy magnetic nanoparticles; The preparation method of the diphenyl ether solution of Co2(CO)8 is as follows: take an appropriate amount of Co2(CO)8, add diphenyl ether at 60°C to dissolve it, and obtain the Co2(CO)8 solution after the Co2(CO)8 is completely dissolved.

3. A novel absorbing material, prepared by the method of claim 1 or 2, characterized in that: The microstructure of the wave absorbing material is based on conductive polymer nanotubes, and the outer surface of the conductive polymer nanotubes is compounded with metal magnetic nanoparticles by a chemical method; the metal magnetic nanoparticles are bonded to the surface of the conductive polymer nanotubes by a ligand substitution reaction; The conductive polymer nanotube is made of conductive polymer material, including any one of polypyrrole, polyaniline, polyethylenedioxythiophene, and polythiophene; the conductive polymer nanotube has a one-dimensional cavity structure, and the cavity diameter is 100-400nm; The metal magnetic nanoparticles are any one of CoFe, FePt, NiFe, NiPt, FePd and FeRu particles, wherein the component ratio of CoFe, FePt, NiFe, NiPt, FePd and FeRu particles can be controlled; and the particle size of the metal magnetic nanoparticles is less than 10 nm.

4. An application of the novel absorbing material as claimed in claim 3, characterized in that: The wave absorbing material can be applied to electromagnetic shielding materials, military stealth materials, electrode materials, molecular wires, sensors, and supercapacitors.

Citation Information

Patent Citations

  • Preparation of magnetic conductive polyaniline nanometer composite material

    CN101280106A